2014
DOI: 10.1109/joe.2013.2245273
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Acoustic Communication With an Orthogonal Signal Division Multiplexing Scheme in Doubly Spread Channels

Abstract: Underwater acoustic (UWA) communication is an ongoing challenge because of the heavy time spread by multipath and Doppler spreads. Here we propose a UWA communication system using orthogonal signal division multiplexing (OSDM), a scheme that measures the multipath profile without an adaptation or interpolation process, to achieve stable communication in doubly spread channels. We previously evaluated the performance of an OSDM scheme in a UWA communication system in both an experiment and simulations. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…The proposed system had far better performance than the traditional decision feedback equalizer (DFE) in a channel with severe frequency selective fading, and its energy efficiency was 3 dB better than a system which uses a pilot signal. A UWA communication system using orthogonal signaldivision multiplexing (OSDM), a scheme that measures the multipath profile without an adaptation or interpolation process, to achieve stable communication in doubly spread channels was proposed in [60]. It was suggested that OSDM could provide a highly reliable communication environment for UWA communication with multipath and Doppler spread, such as in shallow water.…”
Section: Channel Estimation and Equalization Techniques For Multimentioning
confidence: 99%
“…The proposed system had far better performance than the traditional decision feedback equalizer (DFE) in a channel with severe frequency selective fading, and its energy efficiency was 3 dB better than a system which uses a pilot signal. A UWA communication system using orthogonal signaldivision multiplexing (OSDM), a scheme that measures the multipath profile without an adaptation or interpolation process, to achieve stable communication in doubly spread channels was proposed in [60]. It was suggested that OSDM could provide a highly reliable communication environment for UWA communication with multipath and Doppler spread, such as in shallow water.…”
Section: Channel Estimation and Equalization Techniques For Multimentioning
confidence: 99%
“…Despite recent advances in underwater signal processing [20], the underwater acoustic channel will always be very limited relative to terrestrial communication standards. Even though a few publications report point-to-point data rates in the 1 to 10,000 bits/s range, reliable underwater communication is often achieved at much lower rates: 4-100 bits/s for point-to-point communication [21] and 8-40 bits/s for endto-end network communication between 5 to 9 nodes [22] separated by 1 km.…”
Section: Autonomy and Networking Known Limitations And Trends A Pmentioning
confidence: 99%
“…A Doppler-resilient orthogonal signal division multiplexing technique was proposed. That multiplexes several data vectors and a pilot vector into a data stream to fully exploit the frequency-time diversity in the time-variant channels [20], [21].…”
Section: Introductionmentioning
confidence: 99%